The Concept Of Management And Utilization Of The Islamic Education Budget At SD Islam Al Maarif 01 Singosari - Suci Hidayati; Samsul Susilawati; Weyldan Bisri Habibi; Nyak Dara Najmatus Subhi; Mulyono Mulyono (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
Education funding is a fundamental factor in the implementation of education because it is related to the use of the budget or operational financing as a whole. In financing Islamic education, an even and balanced concept is needed which must be considered in managing the budget. This research aims to analyze the concept of management and utilization of the Islamic education financing budget at Al Maarif 01 Singgosari Islamic Elementary School, Malang district. The approach uses descriptive qualitative data collection techniques in the form of field observations, interviews, and documentation related to the administration of management and utilization of the budget in the education unit. The research results show that the management and utilization of the education budget have been adjusted to the technical guidelines (JUKNIS) that have been set. Management of the education budget at Al Maarif 01 Singgosari Islamic Elementary School has been carried out by the concept of Islamic education financing management which begins with financial planning (budgeting) through a financial budgeting process that is carried out the stages in a systematic manner and considers balance and equity in the aspects subject to the budget. The process of financial oversight begins with compiling a RAPBS that has been adapted to the needs of the school. Supporting and inhibiting factors in managing Islamic education financing at Al Maarif 01 Singosari Islamic Elementary School, namely: (1) The school has the right to arrange operational and non-operational financing according to needs, (2) Everything related to reporting is the personal responsibility of the financial manager ( school treasurers) and school principals who are assisted by operators (3) utilization of funding sources from the government in the form of BOS (School Operational Assistance) and BOSDA (Regional School Operational Assistance) is still not optimal and evenly distributed because the disbursement of funds within three months and less on time and (4) committee contributions in the form of tuition fees are still not current so parents need to be more aware of and play a role in financing education. Keywords: Management, Budget, Islamic Education